Kesenjangan Intensi dan Perilaku Berwirausaha : Analisis Keberlanjutan Usaha Mahasiswa di Tasikmalaya - Novita Dewi Gunawan; Rina Madyasari; Alfin Nur Arifah; Ardhiansyah Ardhiansyah (Pusat Riset dan Inovasi Nasional, 2026)
The sustainability of student-run businesses remains a significant challenge despite the implementation of various entrepreneurship development programs in higher education institutions. Many student entrepreneurs discontinue their businesses due to difficulties in transforming entrepreneurial intentions into consistent entrepreneurial behavior and sustainable business practices. This study aims to examine the influence of entrepreneurial intention and entrepreneurial behavior on the sustainability of student businesses in Tasikmalaya. A quantitative approach with a causal-associative research design was employed to analyze the relationships among the research variables. Primary data were collected through structured questionnaires distributed to 100 students who had current or previous experience in operating a business. The collected data were analyzed using appropriate statistical techniques to determine the magnitude and significance of the relationships between variables. The results demonstrate that both entrepreneurial intention and entrepreneurial behavior have a positive and statistically significant effect on business sustainability. Among the two independent variables, entrepreneurial intention exhibits a stronger influence than entrepreneurial behavior, indicating that students with stronger entrepreneurial aspirations are more likely to maintain sustainable business activities. These findings suggest that the sustainability of student businesses depends not only on the willingness to become entrepreneurs but also on the ability to translate entrepreneurial intentions into effective business management practices. The study highlights the importance of strengthening entrepreneurial motivation and practical entrepreneurial competencies through higher education programs to support long-term student business sustainability.